Apuntes teóricos para soportar las articulaciones y tensiones de la educación en el siglo XXI: Theoretical Notes to Support the Articulations and Tensions of Education in the XXI Century - Reyes Pastor, Graciela Esther; Rodríguez-Balcázar, Susan Cristy; Durand Azcárate, Luis Augusto (Universidad del Zulia, 2021)
Peace and justice constitute an ethical and political imperative, articulated with educational narratives and practices, in order to shape new gnoseological, axiological and ontological paradigms, capable of supporting the structure of education in the 21st century, as well as its challenges, challenges and opportunities from different perspectives: constructivist, cooperative and solidary in accordance with the practical and interactive sense of society, to develop critical thinking in the learning process, not deterministic, supported not exclusively by orders of the logical and rational scope, but rather It requires considering the importance of the indeterministic, relational or analogical sphere that feeds life with narratives, stories, images, rituals and aesthetics, among others.